The Different Challenges in Being an Adult Versus a Pediatric Intensivist. (1st March 2022) - Dennis, Diane; van Heerden, Peter; Khanna, Rahul; Knott, Cameron; Zhang, Simone; Calhoun, Aaron
Abstract : OBJECTIVES: There is little current research comparing stress, burnout, and resilience in pediatric and adult intensive care practitioners. This article analyzes data derived from a 2018 qualitative study of burnout and resilience among ICU providers to explore differences that may exist between the pediatric and adult domains of practice. DESIGN: This study represents a thematic subanalysis of textual data derived from a larger qualitative study of ICU provider burnout and resilience. SETTING: Six international critical care units (Australia, Israel, United States). SUBJECTS: Physicians working at the above sites who had been practicing as intensivists for a minimum period of 4 years. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Data were collected using a semistructured interview process, and resulting transcripts were analyzed using postpositivist framework analysis. A secondary analysis was then performed separately on pediatric and adult datasets using the initial coding framework as a template. Three themes related to perceived differences were noted: differences in the patient characteristics within both cohorts, differences in the relationships between staff and family, and personal biases of individual intensivists. Pediatric and adult practitioners differed in their perceptions of the patient's perceived responsibility for their illness. Emotional responses to the stressor of child abuse (particularly as they related to clinician-family relationships) also differed. The stress of dealing with family expectations of patient survival even in dire circumstances was unique to the pediatric environment. Both pediatric and adult practitioners commented on the perceived difficulty of assuming the opposite role. Differences in life expectancy and mortality rate were significant factors in this. CONCLUSIONS: Although similar stressors exist within each group, meaningful differences in how these are perceived and personally processed by individual clinicians exist. Better understanding of these differences will assist attempts to enhance the resilience and provide career guidance to aspiring intensive care clinicians.